Respuesta :
Answer:
[tex]x^{4} -y^{4} +6x^{2}y+9y^{2}[/tex]
Step-by-step explanation:
This is just a big multiplication, but it gets more simple when you break it into steps.
First consider [tex]x^{2} (x^{2} +3y-y^{2} )[/tex]. This multiplies out to [tex]x^{4} +3x^{2}y-x^{2}y^{2}[/tex]
Next, [tex]3y(x^{2} +3y-y^{2} )[/tex]. This is [tex]3x^{2}y+9y^{2}-3y^{3}[/tex]
Finally, [tex]y^{2} (x^{2}+3y-y^{2})[/tex]. This is [tex]x^{2}y^{2} +3x^{3}-y^{4}[/tex]
Sum these three expressions together and you get [tex]x^{4} -y^{4} +6x^{2}y+9y^{2}[/tex]
Answer:
Step-by-step explanation:
(x² + 3y + y²)(x² + 3y - y²)
= x²*(x² + 3y - y²) + 3y*(x² + 3y - y²) + y²((x² + 3y - y²)
= ( x²*x² + x²*3y - x²*y²) + [3y*x² + 3y*3y - 3y*y²] + {y²*x² + y²*3y - y²*y²}
= x⁴ + 3x²y - x²y² + 3x²y + 9y² - 3y³ + x²y² + 3y³ - y⁴
= x⁴ + 3x²y + 3x²y - x²y² + x²y² + 9y² - 3y³ + 3y³ - y⁴
= x⁴ + 6x²y + 0 + 9y² + 0 - y⁴
= x⁴ + 6x²y + 9y² - y⁴
Hint:
[tex]x^{2} *x^{2} = x^{2+2}=x^{4}\\\\3y * 3y = 3*3 * y^{1+1} = 9y^{2}\\\\[/tex]